2021
DOI: 10.1021/acscatal.1c02742
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalysis of Al and Zn Sites of Spinel ZnAl2O4 Catalyst for CO Hydrogenation to Methanol and Dimethyl Ether

Abstract: Activation and surface reactions of CO and H2 on spinel ZnAl2O4 catalyst under CO hydrogenation reaction conditions were studied using temperature-programmed surface reaction spectra and in situ diffuse reflectance Fourier transform infrared spectroscopy. CO and H2 activation was found to occur at the Al and Zn sites of ZnAl2O4 catalyst to form active bidentate formate species and reversibly adsorbed hydrogen species for methanol/diemthyl etherproduction, respectively. The hydrogenation of resulting bidentate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Meanwhile, we found that temporal in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) was able to study elementary surface reaction kinetics of catalytic reactions involving stable surface intermediates, such as formate species during CO or CO 2 hydrogenation reactions. 42 In this work, we studied catalytic performance and elementary surface reaction Consistent with the HRTEM results, only the metallic Cu phase was detected in the XRD patterns of ZrO 2 /Cu NCs inverse catalysts (Figure S3) despite the high loadings and large particle sizes of ZrO 2 . XPS results (Figure S4) demonstrated the presence of both Cu + and Cu 0 species on the surfaces of ZrO 2 /Cu NCs inverse catalysts.…”
supporting
confidence: 60%
“…Meanwhile, we found that temporal in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) was able to study elementary surface reaction kinetics of catalytic reactions involving stable surface intermediates, such as formate species during CO or CO 2 hydrogenation reactions. 42 In this work, we studied catalytic performance and elementary surface reaction Consistent with the HRTEM results, only the metallic Cu phase was detected in the XRD patterns of ZrO 2 /Cu NCs inverse catalysts (Figure S3) despite the high loadings and large particle sizes of ZrO 2 . XPS results (Figure S4) demonstrated the presence of both Cu + and Cu 0 species on the surfaces of ZrO 2 /Cu NCs inverse catalysts.…”
supporting
confidence: 60%
“…In recent years, large attention has been refocused on investigating these Cu-based catalysts for the hydrogenation of pure CO 2 or CO 2 -rich gas feeds containing CO. 12–54 This has led to the development of several processes towards large-scale application. 55–59 Nevertheless, hydrogenation with CO 2 -rich feeds usually suffers from product inhibition, reducing the overall activity of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…21 The spinel structure with the composition AB2X4 constitutes one of the most important classes of crystalline compounds in catalysis. [22][23][24][25][26] In the normal spinel structure, A and B cations occupy two different sites in their structure, namely octahedral (Oh) and tetrahedral (Td) sites, without mixing. The spinel oxides have attracted much attention in the field of heterogeneous catalysis including photocatalysis and electrocatalysis thanks to their structure diversities where their characteristics can be tailored by choosing appropriate A and B cations.…”
Section: Introductionmentioning
confidence: 99%